DESCRIBE CLINICOPATHOLOGIC FEATURES AND OUTCOME OF CHRONIC MEDIA OTITIS PATIENT WHOM UNDERGOING ENDOSCOPIC SURGERY AT NGHE AN OBSTERICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objectives: Evaluation of the results of endoscopic tympanoplasty in children at Nghe AnObstetrics and Pediatrics Hospital.Methods: Cross-sectional study, descriptive study with clinical intervention from June 2020 toJune 2022.Result: Preoperative functional symptoms: 96.7% of patients complained of otorrhea, 80% ofpatients experienced hearing loss, 10% of patients suffered from otalgia and headache. The mostcommon TM perforation is pantympanic perforation. The postoperative PTA average was23.72±8.51, which was significantly lower than the mean preoperative hearing level of 35.35±9.52db. Postoperative functional symptoms improved markedly. More details, otorrhea has decreaseddramatically from 96.7% to 0%, hearing loss has felt from 93.3% to 73%, and tinnitus has declinednearly 50% (from 80% to 33%). The percentage of successful tympanic membrane perforationclosure has reached 96.7% while the proportion of failure has been only 3.3%.
Keywords: Chronic otitis media, audiogram, endoscopic tympanoplasty.